Persistence with Insulin Therapy in Patients with Type 2 Diabetes in France: An Insurance Claims Study. Issue 3 (September 2016) - Roussel, Ronan; Charbonnel, Bernard; Behar, Mourad; Gourmelen, Julie; Emery, Corinne; Detournay, Bruno
Abstract Introduction The objective of this study was to document the initiation of insulin therapy in patients with type 2 diabetes mellitus (T2DM) and its maintenance as a function of time after initiation in a French nationwide representative cohort. Methods A retrospective cohort study was conducted on a random sample of ~600, 000 beneficiaries registered in the French national health insurance database. Newly insulin treated T2DM patients were selected. Persistence was defined as remaining on insulin without discontinuation (defined over a 6 or a 12-month period). Results Among 1909 initiations identified in 2012/2013 (basal scheme: 61.8%, basal/rapid: 15%, other schemes: 23.2%) the average age (standard deviation) at initiation was, respectively, 67.5 (14.2), 61.8 (18.1) and 63.2 (18.4) years. Insulin was initiated by general practitioners in 39.3% and prescribed without other antidiabetic drugs in 32.0%. Persistence was studied in 1969 patients initiating insulin in 2011/2012. Among survivors, nearly 25% stopped insulin during the first year (18.4% for basal scheme). Patients discontinuing insulin were younger [64.7 years (18.5) vs 67.3 years (14.3)p  = 0.0003] and less often male (45.8% vs 55.7%, p  < 0.0001). A proportion of 20.2% did not receive any antidiabetic drug over 12 months after discontinuation. These high percentages were only partly explained by transient intensive insulin regimens in acutely ill patients identifiable in the database. Conclusion We observed a high rate of early discontinuation of insulin in T2DM patients (but lower with basal insulin scheme). Further real world studies are warranted to identify factors associated with this poor persistence. Funding This study was supported by Sanofi-France.